Landscape ecology and water management : Proceedings of IGU Rohtak Conference, Vol. 2 - Singh, R.B; Hassan, M.I; Singh, Mehtab (Advances in Geographical and Environmental Sciences, 2014)
The over-exploitation of important earth resources such as land and water has led to a number of environment-related problems all over the world. At the same time, land-use change caused by various human activities has led to extinction of habitats and species of flora and fauna. In this context, the relevance of biodiversity for human survival is becoming a major international political issue as scientific evidence builds on the global health implications of biodiversity loss. These issues are closely linked with the issue of climate change, as many of the health risks due to climate change are associated with fast degradation of biodiversity. This present work focuses on holistic natural resource-based spatio-temporal planning, development and management and considered them as essential to save the degraded ecosystem for sustainable resource management. Contributions are compiled in two volumes: 1. Climate Change and Biodiversity, and 2. Landscape Ecology and Water Management. Geoinformatics along with its tools such as remote sensing and geographical information systems (GIS) have been used in assessing the results of various environmental problems both physical and social. The volume will be useful for geographers, geoscientists, hydrologists, landscape ecologists, environmentalists, engineers, planners, and policy makers.